2018
DOI: 10.3379/msjmag.1801r002
|View full text |Cite
|
Sign up to set email alerts
|

AC Magnetic Field Imaging of Perpendicular Magnetic Write Head without Image Distortion on Alternating Magnetic Force Microscopy using a Cone-Shape FePt-coated Tip

Abstract: The AC magnetic field of a perpendicular magnetic write head having three surrounding shields was successfully imaged without image distortion on our alternating magnetic force microscope (A-MFM) using a newly developed cone-shape Si tip coated with an L10-FePt film. In contrast, a conventional quadrangular pyramidal Si tip coated with the L10-FePt film showed a distortion of the AC magnetic field image for the same magnetic write head.The image distortion depended on the spatial configuration between the tip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…When it comes to resolving nanoscale domain features, magnetic force microscopy (MFM) has proven to be a very powerful technique, 37,38 that is however, largely unexplored concerning imaging of time-dependent domain processes. Few reports are the early measurements of the write head fields in the MHz regime [39][40][41] and the more recent development of sideband MFM. 42 In both cases, MFM is used for a successful mapping of temporal field dynamics, but not for imaging oscillatory spatial DW processes.…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to resolving nanoscale domain features, magnetic force microscopy (MFM) has proven to be a very powerful technique, 37,38 that is however, largely unexplored concerning imaging of time-dependent domain processes. Few reports are the early measurements of the write head fields in the MHz regime [39][40][41] and the more recent development of sideband MFM. 42 In both cases, MFM is used for a successful mapping of temporal field dynamics, but not for imaging oscillatory spatial DW processes.…”
Section: Introductionmentioning
confidence: 99%
“…BiFeO 3 (BFO) (Figure 1) is a demanded multiferroic material with high ferroelectric Curie temperature (T C ) of 1120 K and a high antiferromagnetic Neel temperature (T N ) of 640 K. The most well-known multiferroics (ferromagnetism and ferroelectricity) are compounds obtained by substitution in BiFeO 3 of Bismuth cations by alkaline earth metal cations. (Bi,Ba) FeO 3 is multiferroic material with single phase that exhibits ferromagnetism and ferroelectricity in room temperature [11] and magnetization switching of the (Bi,Ba)FeO 3 thin fi lm fabricated by RF sputtering was performed at room temperature by only applying electric fi eld [12]. This method of magnetization reversal with this material has much merit such as operation in room temperature, operation in only applying electric field and operation with complete magnetization reversal against other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the distribution of magnetic field from the head having three surrounding shields, MFM tip with symmetry shape for the magnetic charge and with high coercivity magnetic film is effective. We had reported the cone-shaped MFM tip with symmetry for the magnetic charge to get a MFM image without distortion 24) . We also had reported that coercivity of the FePt coated MFM tip is lower than the magnetic field generated by the head having three surrounding shields with large head current 24) .…”
Section: Introductionmentioning
confidence: 99%
“…We had reported the cone-shaped MFM tip with symmetry for the magnetic charge to get a MFM image without distortion 24) . We also had reported that coercivity of the FePt coated MFM tip is lower than the magnetic field generated by the head having three surrounding shields with large head current 24) .…”
Section: Introductionmentioning
confidence: 99%